Refugees' career capital welcome? Afghan and Syrian refugee job seekers in Austria - Eggenhofer-Rehart, Petra M.; Latzke, Markus; Pernkopf, Katharina; Zellhofer, Dominik; Mayrhofer, Wolfgang; Steyrer, Johannes (Journal of vocational behavior, 2018)
This study explores how refugees relocate, acquire, and convert cultural, social, and economic capital when entering the Austrian labor market. Drawing on Bourdieu's theory of practice, we conducted 35 semi-structured interviews with Afghan and Syrian refugee job seekers to investigate how the value of the capital forms changes when they move to a culturally distant field, and what strategies they use to develop their career capital portfolio. Findings reveal that (a) all capital forms are strongly devaluated; (b) refugees striving to use their cultural capital encounter unfamiliar labor market rules, occupational identity threats, and status loss; (c) acquisition and conversion of new capital require both the intricate interplay of capital forms and refugees' proactivity. The article concludes with a discussion of theoretical contributions and practical implications for refugee labor market integration. •We conducted 35 semi-structured interviews with Syrian and Afghan refugee job seekers.•Refugees' career capital is radically devaluated when relocated to a remote field.•Refugees face unfamiliar labor market rules, identity threats, and status loss.•Capital acquisition requires proactivity and is subject to the interplay of capital forms.•Labor market integration requires mutual efforts by both refugees and the host society.